Successful Treatment of Unstageable Pressure Ulcer by Using Advanced Wound Dressing - Sri Sunarti (Acta Medica Indonesiana)
This is a case of a 79-year old male, with late stage prostatic cancer, immobilization and having unstageable stage of lumbosacral pressure ulcer. We manage his ulcer locally with an advanced wound dressing. We apply hydrogel as a primary dressing and hydrofiber as secondary dressing. Advanced wound dressings are designed to maintain a moist environment at the site of application, allowing the fluids to remain close to the wound but not spread to unaffected, healthy skin areas. The relevance of the moist wound environment as a factor accelerating the healing process was first observed by Winter in 1962, but only recently has received more serious attention. An effective dressing should protect the wound, absorb exudate, preserve a moist wound base, and remove excess exudate. Design of effective dressings relies on an understanding of the healing process, as well as the specific conditions of a patient and the effect that each material used could have on the wound.